Some results on the spatial behaviour in linear porous elasticity - Ciarletta, M.; Chiriță, S.; Passarella, F. (Archives of Mechanics, 2005)
In this paper we study the spatial behaviour for an extended class of isotropic and homogeneous porous materials for which the constitutive coefficients are supposed to satisfy some relaxed positive definiteness conditions. By using some appropriate measures, we are able to establish results describing the spatial behaviour of transient and steady-state solutions in these enlarged classes of porous materials.